Effect of Flexible Half-Dose Gonadotropin-Releasing Hormone Antagonist Protocol on in vitro Fertilization Outcome in Predicted Normal Responder: A Study Protocol for a Multicentered, Randomized, Non-Inferiority, Parallel Controlled Trial - Ma YJ; Li MY; Song JY; Sun ZG (Dove Medical Press, 2023)
Ying-Jie Ma,1,* Meng-Yao Li,1,* Jing-Yan Song,1,2 Zhen-Gao Sun1,2 1The First Clinical College, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, 250011, People's Republic of China; 2Reproductive and Genetic Center of Integrative Medicine, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, 250014, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhen-Gao Sun; Jing-Yan Song, Reproductive and Genetic Center of Integrative Medicine, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, 42, Wenhua Road (W), Lixia District, Jinan, Shandong, 250014, People's Republic of China, Email sunzhengao77@126.com; hanlingjuzei91@126.comBackground: Gonadotropin-releasing hormone antagonists (GnRH-ant) are widely used in current in vitro fertilization-embryo transfer (IVF-ET), however, whether the lowest daily dose of GnRH-ant is individualized remains unknown. Due to the negative effect of GnRH-ant on endometrial receptivity, lessening the amount of GnRH-antagonists used during controlled ovarian stimulation may be helpful for embryo implantation. As such, a randomized controlled study is essential to validate the feasibility and efficacy of daily GnRH-ant dose reduction to 0.125 mg geared towards providing scientific evidence for guidance in clinical practice.Methods: In total, 620 infertile women undergoing in vitro fertilization will be enrolled in the multicentered, randomized, parallel controlled trial. Based on a computer-generated random list, they will be randomly and equally subdivided into half-dose GnRH-ant group or conventional-dose GnRH-ant group. The primary outcome is ongoing pregnancy ie, intrauterine pregnancy diagnosed by pelvic ultrasonography at more than 12 weeks of gestation accompanied by normal fetal heartbeats. Secondary outcomes include cycle cancellation, premature luteinizing hormone surge, positive pregnancy, embryo implantation rate, clinical pregnancy, early spontaneous abortion, and live birth. The intention-to-treat and per protocol analyses will be used to initially analyze the difference in ongoing pregnancy rate between the two groups, while the multiple imputation method was used to handle missing values in the data.Discussion: At present, no randomized controlled trials (RCTs) have been performed on the use of the half-dose GnRH-ant protocol (0.125mg/d) to improve reproductive outcomes of IVF-ET in predicted normal responder, compared to conventional-dose GnRH-ant protocol (0.25mg/d). Half-dose GnRH-ant protocol might provide a suitable clinical solution for predicted normal responder undergoing IVF treatment. Thus, it is critical to conduct a well-designed RCT to evaluate the impact of a half-dose GnRH-ant protocol on the reproductive outcomes of IVF-ET in predicted normal responder.Trial Registration: This study was registered in the Chinese Clinical Trials Registry Platform on August 29, 2020. (chictr.org.cn; identifier: ChiCTR2000037629). This trial is version 1.3.Keywords: gonadotropin-releasing hormone antagonist, in vitro fertilization-embryo transfer, half-dose GnRH-ant protocol, predicted normal responder, randomized controlled trial